Onsite healthcare worker acceptability and performance of the point-of-care Pima CD4 assay in Dar es Salaam, Tanzania - Mary E. Schmitz; Karen Chang; Nichole Arnett; Luciana Kohatsu; Ruth Lemwayi; Michael Mwasekaga; John Nkengasong; Omotayo Bolu; Fausta Mosha; Larry Westerman (AOSIS, 2019)
Background: Healthcare workers' acceptance of and ability to perform point-of-care testing is important for reliable and accurate results. The Alere Pima™ CD4 assay (Pima CD4) is the CD4 point-of-care test for HIV management in Tanzania. Objectives: To evaluate healthcare workers' acceptance and performance of Pima CD4 testing. Methods: The study was implemented in five high volume sites in Dar es Salaam, Tanzania, in 2011. Trained healthcare workers performed Pima testing using three whole-blood specimens collected from each patient: venous blood, fingerstick blood directly applied to a Pima cartridge (capillary-direct), and fingerstick blood collected in a microtube (capillary-microtube). Using a semi-structured interview guide, we interviewed 11 healthcare workers about specimen collection methods and Pima CD4 acceptability. Quantitative responses were analysed using descriptive statistics. Open-ended responses were summarised by thematic areas. Pima CD4 results were analysed to determine variation between cadres. Results: Healthcare workers found Pima CD4 user-friendly and recommended its use in low volume, peripheral facilities. Both venous and capillary-direct blood were considered easy to collect, with venous preferred. Advantages noted with venous and capillary-microtube methods were the ability to retest, perform multiple tests, or delay testing. Pima CD4 results were trusted by the healthcare workers and were in agreement with laboratory Pima testing. Conclusion: In this point-of-care testing setting, the Pima CD4 assay was accepted by healthcare workers. Both venous and fingerstick capillary blood specimens can be used with Pima CD4, but fingerstick methods may require more intensive training on technique to minimise variation in results and increase acceptability.